Genomic Variations in Probiotic Lactobacillus plantarum P-8 in the Human and Rat Gut - Song, Yuqin; He, Qiuwen; Zhang, Jiachao; Qiao, Jianmin; Xu, Haiyan; Zhong, Zhi; Zhang, Wenyi; Sun, Zhihong; Yang, Ruifu; Cui, Yujun; Zhang, Heping (Frontiers in Microbiology, 2018)
The effects of probiotics on host gastrointestinal health have become an area of particular interest in the field of probiotic research. However, the impact of the host intestinal environment on genomic changes in probiotic organisms remains largely unknown. To investigate, Lactobacillus plantarum P-8, a well-studied probiotic bacterium, was consumed by healthy human volunteers and rats. Then, the persistence and genomic stability of P-8 in the host gut were surveyed. qPCR results revealed that after the consumption of one dose, P-8 could be detected in the host gastrointestinal tract for 4 to 5 weeks. By contrast, after 4 successive weeks of consumption, P-8 could be detected for up to 17 weeks after consumption ceased. In total, 92 P-8 derived strains were isolated from fecal samples and their genomes were sequenced and analyzed. Comparative genomic analysis detected 19 SNPs, which showed the characteristics of neutral evolution in the core genome. In nearly half of samples (n=39, 42%), the loss of one to three plasmids was observed. The frequent loss of plasmids indicated reductive evolution in the accessory genome under selection pressure within the gastrointestinal tract. We also observed a 609-bp 23S rRNA homologous fragment that may have been acquired from other species after intake. Our findings offer insight into the complex reactions of probiotics to the gut environment during survival in the host. The in vivo genomic dynamics of L. plantarum P-8 observed in this study will aid the commercial development of probiotics with more stable characteristics.